Comparison of the combination of recombinant follicle‐stimulating hormone and recombinant luteinizing hormone protocol versus human menopausal gonadotropin protocol in controlled ovarian stimulation: A systematic review and meta‐analysis. Issue 3 (6th July 2020) - Wang, Yuning; Li, Ling; Deng, Ke; Liu, Jiali; Liu, Yanmei; Zou, Kang; Hao, Guimin; Sun, Xin
Abstract: Objective: To systematically review the efficacy of a combination of recombinant follicle‐stimulating hormone (rFSH) and recombinant luteinizing hormone (rLH) protocol versus human menopausal gonadotropin (hMG) protocol in controlled ovarian stimulation (COS). Methods: PubMed, EMbase, The Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, and WanFang Data were searched to collect studies published prior to January 2019 on the efficacy of rFSH combined with rLH versus hMG alone in COS. Two reviewers independently screened the literature, conducted the data extraction, and assessed the risk of bias for all selected studies. Then, Review Manager 5.3 software was used for the meta‐analysis. Results: There were 2767 patients from 9 studies. The results showed that among patients aged >30 years for IUI, the combination of rFSH and rLH was superior to hMG alone in clinical pregnancy rate per patient (relative risk [RR] = 1.47, 95% confidence interval [CI] 1.02 to 2.12) and endometrial thickness (mean difference [MD] = 0.34, 95% CI 0.04 to 0.64). In patients over 30 years old who received IVF, the results tended to favor the combination of rFSH and rLH in clinical pregnancy rate per patient (RR = 4.48, 95% CI 1.15 to 17.46) and live birth rate per started cycle (RR = 1.69, 95% CI 1.96 to 2.71). In patients less than 30 years old who received IVF, the combination of rFSH and rLH was superior to hMG in the number of retrieved oocytes (MD = 3.70, 95% CI 3.27 to 4.13) and inferior to hMG in number of high‐quality embryos (MD = –0.60, 95% CI –0.91 to –0.29). Conclusion: The combination of rFSH and rLH may have better efficacy than hMG alone in COS. However, considering the limited sample size of the included studies, the current evidence is not definitive.